KEBIJAKAN PEMERINTAH KABUPATEN BENGKALIS DALAM PELAKSANAAN OTONOMI DAERAH (STUDI KASUS PROGRAM BERAS UNTUK MASYARAKAT MISKIN OTONOM DI KECAMATAN BENGKALIS TAHUN 2015) - Destri, Tri Novaldy; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
Raskin is part of the poverty alleviation program, the activity-based social protection of the family in the fulfillment of basic needs for the poor. Raskin have multiple functions, namely strengthening the food security of poor families, as advocates for improving the quality of Human Resources (HR), supporting rice farming and other sectors and increase the economic empowerment of the region. Therefore, which is the case in this study is the problem during the distribution of the Autonomous Raskin to RTS-PM. This study aims to describe the implementation of rice for the poor program autonomous District of Bengkalis 2015 and to find out what the factors that cause the occurrence of irregularities in the implementation of policies rice for the poor program autonomous District of Bengkalis 2015.This study uses qualitative research methods to the data types used primary data and secondary data obtained from the data source research informants. Data collected through interviews and documentation, and then analyzed to provide an overview of the research results.The results of this study addressing that policy rice program for poor communities in the District of Bengkalis autonomous going well. Factors that cause aberrations include: data collection RTS-PM is not on target, lack of socialization of the Raskin program autonomous, lack of oversight by the government, the policy goals Raskin autonomous imprecise, the lack of clarity of communication between relevant organizations, and their rejection of the implementers of the policy of autonomous Raskin program.Keywords: Policy Implementation, Regional Autonomy, Raskin